Influence of pyrolytic thermal history on olive pruning biochar and related epoxy composites mechanical properties. (June 2020) - Bartoli, Mattia; Nasir, Muhammad Abid; Jagdale, Pravin; Passaglia, Elisa; Spiniello, Roberto; Rosso, Carlo; Giorcelli, Mauro; Rovere, Massimo; Tagliaferro, Alberto
Olive pruning is waste from olive cultivation and is generally disposed of through incineration. Olive pruning can, however, be salvaged by pyrolysis, which also produces an interesting carbon-based material known as biochar. Biochar has been proved as a suitable filler which improves the mechanical properties of epoxy composites. Despite this, literature has few studied focused on the relationship between biochar thermal history and the properties it induces in related biochar containing composites. In this work, we report a morphological analysis of biochar produced at different pyrolytic high treatment temperatures (400℃, 600℃, 800℃, and 1000℃) using different heating rates (5℃/min, 15℃/min, and 50℃/min). We investigate the effect of different biochar morphology on the biochar epoxy-related composites, proving the tuneability of the mechanical properties of composites according to the thermal history of the biochar employed.